Peran Organizational Citizenship Behavior (OCB) dan Budaya Organisasi Dalam Meningkatkan Kinerja Karyawan di UKM Snak Makroni Cap Bintang Desa Mutih Wetan, Kabupaten Demak - Ilmih, Andi Aina (BISNIS, 2018)
The study was conducted on employees of UKM Sank Makroni Cap Bintang, Mutih Wetan Village, Demak Regency. This research includes the type of field research, which is a research study that takes authentic data objectively. Whereas seen from the type, this research is classified as qualitative research using descriptive method. The research was conducted to determine the role of organizational citizenship behavior (OCB) and organizational culture to improve employee performance. There are five aspects in implementing OCB, namely: Altruism, Conscientiousness, Courtesy and Civic Virtue. While the role of organizational culture will improve employee performance through seven aspects in its implementation, namely: innovation and courageous risk taking, attention, people orientation, team orientation, aggressiveness, stability.